Can Your Students Save the World? Utilizing Pandemic®, a Cooperative Board Game, to Teach Management. (September 2020) - van Esch, Chantal; Wiggen, Todd
This article focuses on using the cooperative board game Pandemic ® to teach management. In Pandemic, players must work together to cure four diseases and save the world. In this article, we suggest how it can be used in the classroom to teach decision making and also give guidance on how the game can help students learn how to reflect and put into practice the leadership, teamwork, goal setting, and ethical theories presented during management, leadership, and organizational behavior courses. Pandemic is a useful experiential teaching tool that engages students in complex decisions.